A new microphthalmic stygobitic Graptodytes Seidlitz from Morocco, with a molecular phylogeny of the genus (Coleoptera, Dytiscidae) - Ribera, Ignacio; Faille, Arnaud (Zootaxa, 2010)
We describe Graptodytes eremitus n.sp. (Coleoptera, Dytiscidae), a depigmented, microphthalmic stygobitic species found in a pool in the deep area of a cave in the High Atlas of Morocco. To establish its phylogenetic position we inferred a molecular phylogeny of the genus Graptodytes Seidlitz, using ca. 1.7 Kb of four mitochondrial genes for 18 of the 23 previously known species and subspecies of the genus. Graptodytes can be separated in three well supported main lineages, 1) the G. flavipes lineage (apex of median lobe narrow in ventral view), 2) the G. granularis lineage (apex of median lobe expanded and strongly asymmetrical in ventral view), and 3) the G. varius lineage (apex of median lobe expanded but symmetrical in ventral view). The G. varius lineage includes the G. aequalis and G. varius groups, the latter including G. eremitus n.sp. as sister to G. delectus Wollaston (Canary Islands) plus the G. varius complex. A molecular clock approach, using a calibration rate of 2.3% divergence/MY for the combined mitochondrial sequence, estimated the origin of the diversification within the genus at ca. 7MY (late Miocene), and the origin of G. eremitus n.sp. at ca. 2 MY (Pliocene-Pleistocene boundary).